Adherence to complementary feeding recommendations for infants and implications for public health. Issue 4 (20th May 2015) - Fegan, Suzanne; Bassett, Emma; Peng, Yingwei; Steel O'Connor, Kathleen
Abstract: Objective: The current study investigates (i) the extent to which breast-feeding and non-breast-feeding mothers follow the Canadian Nutrition for Healthy Term Infants (NHTI) recommendations; (ii) the first complementary foods given and the differences by breast-feeding status; (iii) whether any breast-feeding is associated with earlier introduction to complementary foods relative to non-breast-feeding, after controlling for potentially confounding factors; and (iv) the need for improvements in timing and resources of interventions by examining breast-feeding rates over time and information sources used by mothers. Design: Longitudinal data from the Kingston, Frontenac, and Lennox & Addington (KFL&A) Infant Feeding Survey were used. Mothers completed a survey at the end of their hospital stay and were interviewed by telephone at 2, 4, 6 and 12 months thereafter. Setting: The study took place in the KFL&A region of Ontario, Canada. Subjects: The sample consisted of 325 mothers who gave birth to a live infant of at least 36 weeks' gestation and a birth weight of at least 1500 g at Kingston General Hospital between January and July of 2008. Results: Four in five mothers introduced complementary foods prior to 6 months. Mothers not breast-feeding at 6 months introduced water, juice, infant cereals, fruit and vegetables, and foods not recommended by Canada's Food Guide sooner than breast-feeding mothers. Breast-feeding mothers were more likely to introduce milks appropriately, but had low adherence to giving their infants vitamin D supplements. Conclusions: To support adherence to NHTI recommendations, interventions should be conducted during early infancy and deliver consistent, evidence-based recommendations.